PENERAPAN HUKUM KEBIASAAN SEBAGAI DASAR HUKUM PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL (Studi Putusan: Nomor 233/Pdt.Sus-PHI/2017/PN.Bdg) - Mohamad Fandrian Adhistianto; Neni Sri Imaniyati; Rini Irianti Sundary (Jurnal Privat Law, 2024)
The case that the author will discuss in this article is the decision of the Industrial Relations Court at the Bandung District Court which is registered with case number 233/Pdt.Sus-PHI/2017/PN.Bdg. regarding a dispute of interest regarding the 2017 Basic Salary Increase. The interesting thing in this decision is that the Panel of Judges decided by considering customary law as the legal basis in determining the components and amount of the 2017 Basic Salary Increase. This article is important because it discusses legal issues, namely the regulation customary law in resolving industrial relations disputes and the application of Customary Law in the Industrial Relations Court Decision Number 233/Pdt.Sus-PHI/2017/PN.Bdg. The research method used is normative juridical legal research using a statutory approach, and a case approach. Customary law is known in the process of resolving industrial relations disputes with further regulations regarding customs having to refer to the provisions of Article 1339 and Article 1347 of the Civil Code. The Panel of Judges at the Industrial Relations Court at the Bandung District Court has decided the case registered under number 233/Pdt.Sus-PHI/2017/PN.Bdg. based on customs as stipulated in Article 1347 of the Civil Code.